Exploration on Micro Structural and Durability characteristics of Raphanussativus as an Ingenious Internal curing agent in concoction with Self-Compacting admixtures. (2017) - Rampradheep, G.S.; Sivaraja, M.; Geetha, M.; Saranya, R.; Sathish, R; Vignesh, V; Kavin, G.; Gayathiri, K.; Balaji, M.; Divya
Abstract: Curing and compaction is found to be an essential role in construction to achieve better sustainability effect. But they are not in proper order by the performance of labours as it can be visualized from many construction sites. Descriptive made on natural item from the ground called Radish also termed as Raphanussativus, an innovative Self-Curing agent was developed and the designed percentage of the curing agent was incorporated in Self-Compacting Concrete is manifested in this paper. Here, the analysis was made for natural self-curing agent concoction with combination of water reducing and viscosity based admixtures like Super Plasticizers and Viscosity Modifying agent in the name Master Glenium Sky8233. The main genesis beyond the intention of radish as a Self-Curing agent is the region of bond water in and its effectual existence of hydroxyl and ether group in a chemical structure of radish family. The design grade of concrete was affixed as M40 and its conceived procedure for such modern concrete was merely based on trial and error and its final upshots were verified with the EFNARC specifications. Upshot from other curing agent such as Poly-Ethylene Glycol (PEG) and conventional methods are compared with the outcome from the innovative curing agent. The sample test outcomes have been given, which shower the behaviour of radish as an internal curing agent under a laboratory conditions. The agent used for robotic curing purpose at the start was inspected to probe its water holding capacity analysis. For the minute case, expository study was retrieved using Fourier Transform Infra Red (FTIR) spectrum analyzer. Various tests were composed to scrutinize the workability properties, mechanical properties and durability property of the concrete. To decide the mechanical properties of concrete, tests such as compression test, split tensile test and flexural test and were regulated. Durability characteristics study on carbonation was overseen. Footprints proved that alike Poly-Ethylene Glycol (PEG), extract from radish is also a powerful curing agent and upswing the cement hydration and compressive strength, minimizes the shrinkage and tweaks the durability of concrete whereas the conventional methods necessitate improvement. Their outcomes are discovered to be bearable as per IS standards, EFNARC (European Standards) specifications and ASTM (American Society for Testing and Materials) codal provisions.